2014
DOI: 10.1007/s12160-014-9593-z
|View full text |Cite
|
Sign up to set email alerts
|

Which Behaviour Change Techniques Are Most Effective at Increasing Older Adults’ Self-Efficacy and Physical Activity Behaviour? A Systematic Review

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractBackground. Increasing self-efficacy is an effective mechanism for increasing physical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
374
3
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(422 citation statements)
references
References 74 publications
17
374
3
9
Order By: Relevance
“…Reference Outcome BCT associated with greater effectiveness of interventions BCT associated with lower effectiveness of interventions Lara et al (38) Increasing fruit and vegetables among older adults 'Barrier identification/problem solving' 'Plan for social support/social change' 'Goal setting (outcome)' 'Use of follow-up prompts' Olander et al (76) Increasing PA in obese individuals 'Teach to use prompts/cues' 'Prompt practice' 'Prompt rewards contingent on effort or progress towards behaviour' French et al (77) Increasing PA in obese individuals None 'Setting behavioural goals' 'Prompting self-monitoring of behaviour' 'Planning for relapses' 'Providing normative information' 'Providing feedback on performance' Gardner et al (78) Reduce gestational weight gain…”
Section: What Is the Best Basis For Personalisation Of Dietary Advice?mentioning
confidence: 99%
“…Reference Outcome BCT associated with greater effectiveness of interventions BCT associated with lower effectiveness of interventions Lara et al (38) Increasing fruit and vegetables among older adults 'Barrier identification/problem solving' 'Plan for social support/social change' 'Goal setting (outcome)' 'Use of follow-up prompts' Olander et al (76) Increasing PA in obese individuals 'Teach to use prompts/cues' 'Prompt practice' 'Prompt rewards contingent on effort or progress towards behaviour' French et al (77) Increasing PA in obese individuals None 'Setting behavioural goals' 'Prompting self-monitoring of behaviour' 'Planning for relapses' 'Providing normative information' 'Providing feedback on performance' Gardner et al (78) Reduce gestational weight gain…”
Section: What Is the Best Basis For Personalisation Of Dietary Advice?mentioning
confidence: 99%
“…A study by Sillence et al (2007) found that sites that provide these social identification cues (where the sites were acknowledged to be written by people similar to themselves and were obviously aimed at 'people like them') claimed to encourage more interest and to be more appreciated. French et al (2014) shared the notion as their study observed that similar others modelled the behaviour associated with increased physical activity.…”
Section: Establishing Sense Of Similaritymentioning
confidence: 62%
“…In contrast, however, the study found that people with low self-efficacy were less likely to be physically active, even if they had social support. Based on a recent systematic review by French et al (2014) on effective behaviour change techniques targeting older adults, the phenomenon was due to poor health and lack of physical abilities among fairly inactive individuals, clarifying why interventions involving the reception of normative feedback (social comparison persuasive principles) may be demoralizing.…”
Section: Personalizing Persuasive Design Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Stralen, De Vries, Mudde, Bolman, and Lechner's (2009) literature review shows that action planning predicted physical activity and that coping planning predicted long-term physical Morais, Encantado, Santos et alactivity initiation and maintenance. However, according to French, Olander, Chisholm, and Mc Sharry (2014), to plan or control behaviour may require more effort which in turn may explain the smaller results observed in physical activity interventions with older adults, possibly due to decreases in executive function in this specific age group. Additionally, goal setting and self-monitoring using a pedometer is a behavioural based intervention that seems to be associated with significant increases in physical activity (Bravata et al, 2007), long-term changes in physical activity behaviour (Chase, 2013), and working as a possible motivational strategy to maintain older adults in physical activity interventions (McMurdo et al, 2010).…”
mentioning
confidence: 99%